2005
DOI: 10.1158/1055-9965.epi-04-0230
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Risk Factors Associated with Clearance of Type-Specific Cervical Human Papillomavirus Infections in a Cohort of University Students

Abstract: Background: Previous findings regarding risk factors for human papillomavirus (HPV) persistence, other than viral determinants, identified from prospective cohort studies have been inconsistent in part because study designs have differed with respect to differing HPV detection methods and varying lengths of follow-up time. Therefore, the objectives of this study were to continue the search for epidemiologic risk factors of persistent cervical HPV infections and determine what behaviors differed between those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
2
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 48 publications
6
69
2
7
Order By: Relevance
“…However, only few of the studies included in that review (18) could allow for the possible confounding effect of sexual activity or provided information on long-term OC use. Among the studies not included by Green et al, two large studies (12,19) showed a direct association, one showed an inverse association (20), and several others (10,13,21,22,46,47) showed no relationship between HPV positivity and OC use.…”
Section: Discussionmentioning
confidence: 93%
“…However, only few of the studies included in that review (18) could allow for the possible confounding effect of sexual activity or provided information on long-term OC use. Among the studies not included by Green et al, two large studies (12,19) showed a direct association, one showed an inverse association (20), and several others (10,13,21,22,46,47) showed no relationship between HPV positivity and OC use.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, though none of the longitudinal studies of coinfections have identified condom use as a significant predictor, it was associated with decreased occurrence of coinfections in two cross-sectional studies (18,41). Although condom use has not been found to have the consistent protective effect with HPV that it has with other STIs (42,43), it is likely that when used properly, condoms convey at least some degree of protection, either by acting as a protective barrier against skin-to-skin transmission or by decreasing HPV viral load (34). OC use has also been found to have an equivocal effect on coinfection risk (15,16); however, it is also strongly associated with sexual activity, and residual confounding may exist even after adjusting for number of sexual partners (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, however, modifiable factors such as smoking status, vegetable consumption, and condom use have also been associated with the occurrence of HPV more generally (33,34), though studies of these factors in relation to coinfections have been mixed (8,(14)(15)(16)18). As such, the aim of this study was to investigate the influence of both biologic and behavioral predictors on the acquisition of HPV coinfections, with a particular focus on HLA alleles as candidate immune factors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently IARC has classified combined oral contraceptives as carcinogenic to cervix and risk is related with increase duration of use (>10 yrs) 18 . The association between smoking and HPV persistence is less consistent [22][23][24] . But IARC has classified tobacco smoking as a cause of cervical cancer 25 .…”
Section: Risk Factors For Hpv Infection and Neoplasiamentioning
confidence: 99%
“…Evaluation of relationship between condom use and HPV infection have failed to demonstrate a protective effect of condoms because HPV infections is transmissible through contact with areas of unprotected genital skin 21 . [22][23][24] . But IARC has classified tobacco smoking as a cause of cervical cancer 25 .…”
Section: Risk Factors For Hpv Infection and Neoplasiamentioning
confidence: 99%